Mogućnosti i budućnost bh. društva / Options and Future of B-H Society - Čerkez, Mirza (Pregled: časopis za društvena pitanja / Periodical for social issues, 2014)
Article of Scientific Debate on the Social Processes in Bosnia and Herzegovina on its Path of EU Ascension, 22 April 2014.